Interactive solat multimedia courseware (I-Solat) / Mohamad Imadi Mohamad Nor - Mohamad Nor, Mohamad Imadi (2014)
Solat is obligatory to every muslim. Some people feels that they need to reevaluate the way they perform solat thus opt for various means to find information. One of the medium to deliver information regarding solat is via courseware. From the preliminary study conducted, it is found that the existing solat courseware does not give detail explanations on how to perform solat in a correct way, most of the available courseware does not provide comprehensive contents. Interactive Solat Multimedia Courseware (i-Solat) is presented to improve the understanding in learning solat by showing user the correct way to perform solat. In addition, the i- Solat Courseware has been accompanied with the facts from the science perspective on how solat movements can benefit our body. The courseware can perform as a complementary tool to assists users learn about solat because it covers comprehensive contents from performing ablution to reciting doa. i-Solat is developed based on ADDIE Model which comprises of Analysis, Design, Development, Implementation and Evaluation phases. Another two phases are added which are Preliminary Study and Documentation to complete the project. Evaluation of the i-Solat courseware has been conducted to 30 respondents and to 2 Subject Matter Exper (SME). The evaluation consist five constructs that has been done which focuses on the user interface satisfaction, usability and the content of the courseware. Analysis from the respondents shows that the highest mean is 3.57 with standard deviation 0.504, indicates that the usability of the courseware is accepted mostly by all respondents. However, the courseware still needs further enhancement to make it more effective, interactive and more comprehensive.